Implementasi Green Management dalam Meningkatkan Keunggulan Kompetitif Perusahaan - Wendy Liana (Lembaga Pengembangan Kinerja Dosen, 2025)
Green Management has become an important strategy for companies to face environmental challenges while increasing competitiveness in the global market. This study aims to analyze the implementation of Green Management as a strategic approach in increasing the company's competitive advantage. The research method used is a literature review of various relevant previous studies, including the concept of Green Management, its impact on operational efficiency, product innovation, and corporate image. The results of the analysis show that the adoption of Green Management contributes significantly to reducing operational costs through energy efficiency and waste management. In addition, companies that implement sustainable practices succeed in creating added value for consumers, increasing customer loyalty, and strengthening market positions. This study also identifies several challenges, including initial implementation costs and organizational resistance, which can be overcome through government policy support and increasing environmental awareness among stakeholders. Thus, Green Management not only supports environmental sustainability goals but also provides strategic advantages for companies in the long term.